Logistic performance assessment systems: Structuring, challenges and development opportunities - Santos, Lucas de Oliveira; Nunes, Denilson Ricardo de Lucena; Melo, André Cristiano Silva; Carneiro, Mariana Pereira; Martins, Vitor William Batista (Brazilian Journal of Operations & Production Management, 2020)
Goal: The purpose of this article is to encourage discussion on the basic structuring of a logistics performance assessment system, as well as the challenges and opportunities identified in the development and implementation of new proposals. Design / Methodology / Approach: A systematic literature review was adopted as a research strategy, based on a protocol adapted to the theme of this research. The bases searched were Scopus, Web of Science, Scielo and Science Direct. Results: It was possible to identify a basic structure for the elaboration of a logistic performance evaluation system. In addition, a number of opportunities for developing the theme were observed, as well as the respective challenges to be overcome. Limitations of the investigation: One of the limitations found was that the databases chosen did not always have articles available in their entirety, five of them were not available. Practical implications: It is believed that this research can serve as a reference for researchers who are interested in proposing performance evaluation systems in the context of logistics, contributing to an initial understanding of its structure and highlighting the possible implementation challenges. Originality / Value: According to the bases surveyed, this is the first survey that sought to identify the structure of the logistic performance assessment systems with a focus on business logistics.